The Brand Development of Nagiwa - Nurhasanah, Fitri Rizki; Mutiaz, Intan R (The Indonesian Journal of Business Administration, 2013)
Indonesia's population reaches more than 230 million people with the majority (85%) are Muslim. This is potential market for a company that would do business in Islamic clothing. One of the cities that are shopping center is Bandung. This city has a number of factory outlets, trade centers, and malls. Nagiwa is one of the companies engaged in the business of Muslim clothes. Nagiwa has been in the Muslim fashion business since 15 years ago. Nagiwa currently has several stores in Pasar Baru Bandung, and some resellers that are outside Bandung. But until now, Nagiwa’s brand awareness is very low due to the lack of uniqueness as well as high level of competition. This high competition can be seen from the number of Muslim clothing sellers in Pasar Baru Bandung, reached 60% of the total existing merchants. This causes Nagiwa‘s market share becomes small. Methodologies used in this study are interviews and questionnaires in order to find new strategies that should be done. Interviews are done to the owner of Nagiwa and manager of Pasar Baru. The questionnaires on the other hand are given to teenage school students in Bandung. The purpose of interviews and surveys is to find strategies to solve root cause of Nagiwa’s problem, which are the low brand awareness and small market share. Strategy used to increase market share and brand awareness is to create a new brand extension for Nagiwa. The brand extension is Larova. The difference between Larova and Nagiwa is the target market; teenagers for Larova. This is because there is no company that sells Muslim specifically for youth, while the number of teenagers in Bandung is high. To obtain high brand awareness, marketing strategy activity is made through social media. Strategies that would be used is by cooperating with fashion bloggers and web stores. Furthermore, products-sounding is also done on Facebook, Twitter, Instagram, and blog / Tumblr. The implementation of this strategy is done in a period of one to two years. Next, if this strategy is successful, the implementation is conducted in the medium-term strategy. But if it does not work, exit strategy is executed in the form of re-analyzing new root causes or developing the parent business (Nagiwa).